PREVENTION OF DOMESTIC VIOLENT IN HOUSEHOLDS: PREVENTIVE AND INSTITUTIONAL APPROACHES - RATNAWATI; HERYANI, WIWIE; SUCI WAHYUNI, ANDI; MUHAMMAD ASWIN ANAS, ANDI (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Domestic violence is a criminal offense as regulated in the Law of Domestic Violence Elimination. Domestic violence still occurs in various regions, including South Sulawesi, Wajo Regency. This situation is concerned by the government and the local community. The issue of domestic violence not only causes polemics for perpetrators and victims but also for the community. These problems can also be a source of violations of social norms and other legal norms. For this reason, the available legal highlight requires preventive measures from both the central and regional governments and all elements of society. Dissemination of the Domestic Violence Act discusses criminal acts in domestic violence in terms of forms of domestic violence, criminal sanctions for perpetrators, victims' rights and domestic violence handling by local governments through particular institutions or units for protection and handling of victims of domestic violence. With the socialization of this law, it is expected to be able to prevent and minimize the occurrence of cases of domestic violence and to provide changes in the life values ​​of the local village community.